17-16(7/8x+-2)=7(7-2x)

Simple and best practice solution for 17-16(7/8x+-2)=7(7-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17-16(7/8x+-2)=7(7-2x) equation:



17-16(7/8x+-2)=7(7-2x)
We move all terms to the left:
17-16(7/8x+-2)-(7(7-2x))=0
Domain of the equation: 8x+-2)!=0
x∈R
We add all the numbers together, and all the variables
-16(7/8x-2)-(7(-2x+7))+17=0
We multiply parentheses
-112x-(7(-2x+7))+32+17=0
We calculate terms in parentheses: -(7(-2x+7)), so:
7(-2x+7)
We multiply parentheses
-14x+49
Back to the equation:
-(-14x+49)
We add all the numbers together, and all the variables
-112x-(-14x+49)+49=0
We get rid of parentheses
-112x+14x-49+49=0
We add all the numbers together, and all the variables
-98x=0
x=0/-98
x=0

See similar equations:

| -5t^2+30t+60=0 | | x(x^2-x)=343 | | 58=50+c-40/4 | | -6+x/3=-10 | | 2p+2-9p-9=-4 | | 3q^2+40q+13=0 | | 200=16(6t-3 | | x^2/x+80=40 | | 1/2t+4=3 | | 3/2*n=2/9 | | (5x-17)=(3x+14) | | 5x+5×=5×+4 | | 9v/15=0 | | 15j=3/11j | | -4x+6=-8x+30 | | 2x+8=12x+6 | | 2(6)+x=14 | | 6x-4(5)=34 | | a–5/6=-32/3 | | 12x-13x-17=19 | | 12v-8v=32 | | 0=6.5+42x-4.9x^2 | | 580=26n+8 | | -6v+1=43 | | 69=21^x | | 2/3h-156=13/24 | | a–5/6=-32/3= | | 3a+9=2a-1 | | (8,-8)m=1/8 | | 0.2(5x−6)+2x=0.8 | | 1/2t=4=3 | | -16-8n=-10 |

Equations solver categories